Pengaruh Motivasi Terhadap Hubungan Partisipasi Anggaran Dengan Kinerja Manajerial (Studi Kasus Pada PT. Indonesia Power) - Sumaryati, Anna (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2011)
This research to test influence of motivation on the relationship with managerial performance budget participation (Case Study at PT. lndonesia Power). Research with the method survey by questionary to 38 manager. Intake sample by saturated sampling. While technique analysis the, data with regression Analysis of Moderating. Result of research about the impact of motivation on the relationship with the budget participation on managerial performance PT Indonesia Power is as follows: participation budget significant efect on managerial performance, can be defined with greater participation in the preparation of the budget will improve the managerial performance of PT. Indonesia Power. The existence of budgetary participation and motivation interaction significant effect on managerial performance, This could be interpreted by the high motivation in the work will be able to streng then the influence of budgetary participation on managerial performance PT. Indonesia Power.Keyword : managerial, performance, budget, participation,motivation